Childhood, racism and school education: a study of scientific productions published in Oasisbr (2013-2023) - Lenina Lopes Soares Silva; Isabel Cristina de Jesus Brandão; Milene de Macedo Sena (University of Bologna, 2024)
Structural racism in Brazilian society penetrates institutions and has affected school education in childhood. In view of this, studies on racism and diversity by several authors (Souza, 2021; Munanga 2022; Mellino, 2019; Ribeiro, 2017; Abramowicz, 2013) are considered to problematize the ethnic-racial relations that are established in the school space. The objective, therefore, is to analyze scientific productions about childhood, racism and school education, seeking to identify issues/problems/solutions that involve the topic in everyday situations in schools. This is a state of knowledge survey (Morosini et al., 2021), using as its source the Oasisbr platform of the Brazilian Institute of Information, Science and Technology, using the descriptor composed of the triad: childhood, race and school education, which resulted in 48 articles, of which 19 articles were selected for analysis. It is noteworthy that two refer to racism in Colombia, some refer to the reality in Brazil, and 17 are about experiences of racism in Brazilian schools, mainly in early childhood education. It is concluded that the works indicate the need to build decolonizing and anti-racist pedagogical practices in schools.